PENGARUH MIKORIZA DAN ARANG PADA MEDIA TUMBUH TERHADAP PERTUMBUHAN SEMAI MAHONI ( Swietenia macrophylla King.) - Lisda, Lisda; Umar, Husain; Yusran, Yusran (Universitas Tadulako, 2016)
Mahogany (Swietania macruphylla King) is an introduced timber species and a priority in the current development of plantation forests. This species has a quite good market in the timber trade in indonesia. It is used as material for furniture, building and construction. Charcoal contains C (carbon) elements, and pores containing hydrocarbons and other organic compounds, i.e. water,Â nitrogen , and sulfur. The objective of this study was to determine the effect of mycorrhizal and charcoal on growth media on the mahogany (Swietenia macrophylla King.) seedling growth. The study was conducted from March to May 2014 in Permanent Nursery of BPDAS Palu-Poso- Tadulako University, Palu, Central Sulawesi. This study was organized with a completely randomized design (CDR), which consisted of 7 treatments, namely: MO = top soil media without mycorrhiza (control); M1= top soil + micorrhiza; AK = top soil + wood charcol; AT = top soil + coconut shell charcoal; MAK = top soil + mycorrhiza + wood charcoal; MAT = top soil + mycorrhiza + coconut shell charcoal; MKT = top soil + mycorrhiza + wood charcoal + coconut shell charcoal. These treatments were replicated five times each, so tge total sample were 35 experimental units. The honestly significant difference test (HSD) was used to determine the difference between treatments. The study result indicate that treatments (mycorrhizal soil, wood charcoal, coconut shell charcoal, wood charcoal + mycorhizal, coconut shell charcoal+ mycorrhizal, wood charcoal mycorrhizal + coconut shell carcoal) might increase significantle growth of mahogany seedlingsÂ compared to the control (without application of FMA). The seven treatments give significant difference to the height, number of leaves, and the diameter of mahogany seedling except for the control treatment.Key words: Mahogany (Swietenia macrophylla King), Mikoriza, Seedling growth